1,4-dioxane-fused 4-anilinoquinazoline as inhibitors of epidermal growth factor receptor kinase - Lee, JY; Park, YK; Seo, SH; So, IS; Chung, HK; Yang, BS; Lee, SJ; Park, H; Lee, YS (WILEY-V C H VERLAG GMBH, 2001)
The 4-anilinoquinazoline PD 153035 (1) is a potential antitumor agent which acts by inhibiting tyrosine kinase activity of epidermal growth factor receptor (EFGR) via competitive binding at the ATP site of enzyme. A series of cyclic analogues of PD 153035 bearing the 1,4-dioxane ring was prepared by reaction of 6-chloro derivative 5 with several aniline nucleophiles. These were evaluated for their ability to inhibit the EGFR kinase and the growth of primary human tumor cell cultures. All of the new 4-anilinoquinazolines exhibited less potency than PD 153035 against EGFR kinase. However, compounds 2b, 2c, 2e, 2g, and 2h showed higher inhibitory activities than PD 153035 against the growth of A431 tumor cell line. The compound 2b containing 3-chloroaniline ring was as potent as PD 153035 against EGFR kinase and showed about 5.4-fold better potency than PD153035 in the inhibition of growth of A431 cell line with good selectivity.